Antibiotic Prophylaxis in One-Stage Revision of Septic Total Knee Arthroplasty: A Scoping Review - Carlo Ciccullo; Thomas Neri; Luca Farinelli; Antonio Gigante; Rémi Philippot; Frederic Farizon; Bertrand Boyer (MDPI AG, 2023)
Background: Total knee replacement (TKA) is becoming a routine procedure in orthopedic surgery. One of the possible complications of this surgery is periprosthetic joint infection (PJI). The purpose of this study is to identify, through a literature review, which antibiotic is used as prophylaxis for septic one-stage revision TKA and what is the rationale for its use. Methods: We searched: MEDLINE, Embase, PsycINFO on Ovid, the Cochrane Library, and the Google Scholar Database. The searches were limited by date (January 2005 to September 2022) and to the English language. All types of original research were considered, including prospective or retrospective longitudinal studies, cross-sectional studies, and randomized trials. The specific search terms were ((antibiotic [MeSH]) AND (prophylaxis)) and (TKA OR TKR OR "Arthroplasty, Replacement, Knee" [MeSH] OR ((knee) adj2 (replace* OR arthroplasty* OR prosthe*))). Results: Despite our research efforts, we found no article capable of answering the question of which antibiotic to use as surgical prophylaxis for a septic revision one-stage TKA. Conclusions: Although the research results are inconclusive, we would recommend using the same antibiotic prophylaxis as for primary joint replacement, i.e., cefazolin, as it was recommended for its low side effect rate and relative effectiveness.